(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
This paper is based on investigation of nutrient substance balance in three lake-basin in West Poland. This investigation are managed since one year and make possible to estimate amount of nutrient substance in each lake. This project can answer how extensive agriculture influences on surfaces water quality.